Stratification of family vulnerability: Perceptions of Family Health Strategy teams (Research, Society and Development, 2022)
This research aimed to understand the perception of Family Health Strategy team members about the stratification of family vulnerability of attached families. This is a descriptive and exploratory study, with a qualitative approach, carried out with members of the Family Health Strategy teams of a city in Paraná. The information was collected through semi-structured interviews, recorded, guided by the question "Tell me about the stratification of family vulnerability of the attached families". All ethical precepts were respected. After collected, the recorded statements were transcribed in full and submitted to the content analysis technique, in the thematic modality, respecting the stages of pre-analysis, material exploration, and treatment of results. Through this analysis technique, the results were organized by similarity and presented in the following thematic categories Potentialities of the family vulnerability stratification process; Weaknesses of the family vulnerability stratification process; Strategies for possible improvements of the family vulnerability stratification process. We conclude that the findings of this study reveal potentialities and frailties related to the practice of family vulnerability stratification experienced by Family Health Strategy teams, and may drive the implementation of improvements to the stratification process, as a consequence of possible improvement strategies highlighted by the interviewees.